Advancements in RP-HPLC Methodology for Tirzepatide Estimation in Human Plasma: Development, Validation, and Applications - Vaishnavi N.Bitne; Dr.Vinayak M. Gaware (Asian Journal of Pharmaceutical Research and Development, 2025)
Reversed-phase high-performance liquid chromatography (RP-HPLC) is a technique that separates molecules by polarity. It's commonly used in pharmaceutical development and manufacturing, as well as in proteomic research. The goal of the proposed method is to develop and validate a new green and simple liquid chromatographic system for simultaneously quantifying the novel drug terzepatide. A simple, specific, precise and accurate method for quantification of tirzepatide was developed and validated in human plasma and was applied for pharmacokinetics to determination the concentration of tirzepatide in human low dose with different formulation of the tirzepatide. Although, several methods have been developed previously for this drug as reported, but this is the -cost, fast and more accurate as the samples have been prepared by less costly chemicals and procedures, like protein precipitation technique also, use of nitrogen for drying has shown better results compared to earlier methods.